2004
DOI: 10.1212/01.wnl.0000123248.39847.1d
|View full text |Cite
|
Sign up to set email alerts
|

Striatal dopamine transporter in dementia with Lewy bodies and Parkinson disease

Abstract: This study showed differences between PD and DLB in the pattern of striatal dopaminergic dysfunction. DLB patients do not have the characteristic selective degeneration of ventrolateral nigral neurons seen in PD. This could explain some of the clinical differences between DLB and PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
4
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 19 publications
7
92
4
1
Order By: Relevance
“…However, in theory this association could be different in DLB patients. It seems that there is a difference in the predilection of DAT SPECT tracer uptake in the basal ganglia between PD and DLB patients, with DLB patients showing a significantly lower caudate nucleus-toputamen ratio (9,14). Thus, basal ganglia pathology might, after all, differ between DLB and PD patients-results that are supported by Walker et al (9).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, in theory this association could be different in DLB patients. It seems that there is a difference in the predilection of DAT SPECT tracer uptake in the basal ganglia between PD and DLB patients, with DLB patients showing a significantly lower caudate nucleus-toputamen ratio (9,14). Thus, basal ganglia pathology might, after all, differ between DLB and PD patients-results that are supported by Walker et al (9).…”
Section: Discussionmentioning
confidence: 83%
“…We identified only one DAT SPECT imaging study including 15 DLB patients correlating DAT binding (in which 123 I-2-b-carbomethoxy-3b-(4-iodophenyl)-N-(3-fluoropropyl)nortropane [ 123 I-FP-CIT] was used as the radioligand) with parkinsonism. The authors suggested that there might be a difference in the predilection for DAT uptake in PD versus DLB, since the caudate-to-putamen ratio was less reduced in DLB than in PD and, further, no correlation between severity of parkinsonism and DAT binding was found in DLB patients (9).…”
mentioning
confidence: 99%
“…In vivo striatum dopaminergic denervation with loss of presynaptic striatal dopamine transporter (DAT), as measured by single-photon emission tomography (SPECT) and PET, is a consistent finding among patients with probable DLB, compared to clinically normal controls and patients with Alzheimer's disease dementia (Walker et al, 2002(Walker et al, , 2004O'Brien et al, 2004;McKeith et al, 2007). While the dopaminergic degeneration has been widely documented to affect the striatum of patients with DLB (Walker et al, 2004;Klein et al, 2010), a cholinergic network alteration involving the striatum has been postulated in the Lewy body disease spectrum of disorders (Langlais et al, 1993) but its mechanism is still poorly understood (Bohnen and Albin, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…While the dopaminergic degeneration has been widely documented to affect the striatum of patients with DLB (Walker et al, 2004;Klein et al, 2010), a cholinergic network alteration involving the striatum has been postulated in the Lewy body disease spectrum of disorders (Langlais et al, 1993) but its mechanism is still poorly understood (Bohnen and Albin, 2011). In this setting, our finding of an association between higher PiB retention and higher atrophy rates in the caudate and putamen nuclei suggest an accelerated subcortical neuronal injury involving the global PiB SUVR (x-axes) and regional grey matter annualized log Jacobian (y-axes) in patients with DLB, after adjusting for age.…”
Section: Discussionmentioning
confidence: 99%
“…2) (Walker et al, 2002;Donnemiller et al, 1997;O´Brien et al, 2004) and postsynaptic receptors (Walker et al, 1997) has been shown in SB, unlike in AD. Moreover, Walker et al (2004) found a consistent, non-asymmetrical decrease in uptake between caudate and putamen, an observation that could also differentiate this condition from PD. …”
Section: Dementia With Lewy Bodies (Dlb)mentioning
confidence: 58%